PELAKSANAAN BIMBINGAN ROHANI ISLAM DALAM MENGELOLA EMOSIONAL PASIEN DI RUMAH SAKIT ISLAM METRO - Aisyah Khumairo; Adiansyah Adiansyah; Nia Ihromi Tanjung (Jurnal Bimbingan Penyuluhan Islam, 2023)
Islamic spiritual guidance services in fostering the emotional state of internal medicine patients at the Metro Islamic Hospital are motivated by the many problems in the emotional condition of internal medicine patients such as boredom, sadness, disappointment, stress and lack of confidence. The problem in this study is that patients at the Metro Islam Hospital who are given spiritual guidance by counselors experience emotional instability due to their physical condition. The purpose of this study is to explain the implementation of Islamic spiritual guidance services in fostering emotional internal medicine patients at Metro Islam Hospital. This type of research is, field research (Field Research). While the nature of the research is descriptive. The location of this research is Metro Islam Hospital. Data collection techniques used are interviews, observation, and documentation. This study uses the Miles and Huberman model to analyze the research data. The results showed that in the implementation of Islamic spiritual guidance for internal medicine patients at the Metro Islam Hospital there is a service schedule that is carried out every Monday to Friday. The methods used in Islamic spiritual guidance are the direct guidance method and the indirect guidance method. The forms of Islamic Spiritual Guidance Services that are carried out are a) guidance services consisting of tadzkirah guidance, worship guidance, dhikr and prayer guidance, guidance for patients with special needs, and funeral relocations; b) Spiritual consultation services, this service is more focused on patients who experience spiritual problems that can interfere with their psychology; c) Spiritual development services. There are three stages in carrying it out, namely the pre-service stage, the process stage and the post-service stage.